Светодиод с CVD-алмазным теплоотводом; Известия вузов. Физика; Т. 56, № 8, ч. 3 - Вилисов А. А. Анатолий Александрович; Ремнёв (Ремнев) Г. Е. Геннадий Ефимович; Линник С. А. Степан Андреевич; Солдаткин В. С. Василий Сергеевич; Тепляков К. В. Констатин Владимирович (2013, 2013)
Заглавие с экрана